Modeling economic growth in contemporary Russia - Sergi, Bruno S. (Bingley, U.K. : Emerald Publishing Limited, 2019)
Russia is one of the world's largest growing economies. With this exciting new growth and development, there is a wealth of knowledge to be discovered from the strategies and models being used and created throughout Russia's economy.Modeling Economic Growth in Contemporary Russia portrays and sets pieces of Russia's growth strategies to produce an extraordinary record of economic analysis. A leading expert in emerging markets, editor Bruno S. Sergi and a cast of experienced Russian academics offer a wealth of questions and critical examples on Russia that are delivered through a sound framework and provide unique knowledgeable support and interdisciplinary research about modeling a sound growth strategy for Russia. Through various chapters on financial development and economic growth, Sergi explores the fascinating landscape of Russia's economy, including chapters on green investment; education and inclusive development; sustainability; smart cities; international cooperation; and innovation-based growth.For anyone interested in international economics, or students of emerging economies and markets, this is a fundamental study of an area that has never before been studied in such depth.
Prelims -- Financial development and economic growth in Russia -- The bank of Russia: modeling parameters of financial sustainability in low-growth and high-volatility environment -- Financial stability: modeling the Russian budgetary and tax policy with fiscal multipliers' attraction -- How to create competitive organization: leveraging strategic capabilities in Russia -- Russia's transition to an innovation-based growth: problems and opportunities -- Education and inclusive development: puzzle of low-learning equilibrium -- Infrastructure public-private partnership projects: budget consolidation policy in Russia and government expenditures' efficiency increase -- The agro-industrial complex: tendencies, scenarios, and regulation -- Smart cities and economic growth in Russia -- Green investment in Russia as a new economic stimulus -- Index.
Includes index.
Print version record
Keywords: Economic development -- Russia (Federation); Business & Economics -- Development -- Economic Development; Economic growth; Russia (Federation) -- Economic conditions -- 1991-